Superconducting diode effect via conformal-mapped nanoholes - Yang-Yang Lyu (Nature Portfolio, 2021)
A superconducting diode is dissipationless and desirable for electronic circuits with ultralow power consumption, yet it remains challenging to realize it. Here, the authors achieve a superconducting diode in a conventional superconducting film patterned with a conformal array of nanoscale holes.